ExperimentalStudy on Indoor Thermal Comfort of Multi-connected Dry Capillary Radiation Heat Pump - Ma Xiaodan; Wang Mengfei; Pu Yuhang; Song Chentao; Zhuang Dingding; Hong Shiying; Zhou Xinyu; Tu Qiu (Zhileng xuebao)
In traditional capillary radiation air conditioning systems, water is used as the coolantinthe terminalsof the capillary. However, the secondary heat transfer reduces the energy efficiency and freezing of pipes in winter is a potential danger. In this study, a multi-connected dry capillary radiation heat pump (MDCHP) with refrigerant as the cooling medium has been proposed. Thermal tests of the unit were undertaken in winter at the experimental platform of the Ningbo Institute of Engineering. Indoor dry and wet bulb temperature, and air velocity in heating mode were tested for ducted air conditioning unit and MDCHP respectively when the target condensation temperature was set to 48 ℃.The thermal comfort of the two heating terminals were compared and analyzed with the thermal comfort evaluation index of PMV-PDD. During an 8 h running period of the MDCHP, the indoor temperature field distribution was uniform, the maximum horizontal temperature difference at 1.5m was0.56 °C, and the maximum vertical temperature difference was0.37 °C. During the process of oil return, the temperature drop was less than 1 °C, the relative humidity was maintained at 60%–65%, and the thermal comfort index of PMV and PDD were maintained at-0.5–0.0 and0%–10%, respectively. These results demonstrated that the MDCHP can achieve a First Class standard of thermal comfort and every comfort index was superior to that of ducted air conditioning unit.